Two cases of unresectable hepatocellular carcinoma treated via atezolizumab and bevacizumab combination therapy - Ryosuke Tsunemitsu; Motoyasu Tabuchi; Shinya Sakamoto; Kenta Ogi; Manabu Matsumoto; Jun Iwata; Takehiro Okabayashi (Surgical Case Reports)
Abstract Background Treatment of hepatocellular carcinoma (HCC) varies widely depending on the patient's condition. In recent years, combination therapy with immune checkpoint inhibitors has emerged as the treatment of choice due to its superior antitumor effects for unresectable HCC (uHCC). Conversion surgery (CS) after systemic chemotherapy is expected to be an effective treatment strategy for uHCC. Here, we report two cases of uHCC with bilateral porta hepatis invasion, in which atezolizumab plus bevacizumab therapy regressed the tumor invasion of the porta hepatis, followed by CS with R0 resection. Case presentation The first patient—a 71-year-old man with S4 HCC—developed porta hepatis, and the tumor compressed the right portal vein and bile duct. R0 resection with left trihepatectomy was impossible because of insufficient liver function, and combination therapy using atezolizumab and bevacizumab was initiated. After ten courses of treatment, the tumor shrunk with regression of the porta hepatis contact, and segmentectomy of S4 was performed with a sufficient surgical margin. Histopathological findings showed that the primary tumor was mostly necrotic with no residual viable tumor cells. The second patient was a 72-year-old man with an S4 HCC extending to the porta hepatis. The patient’s condition was almost similar to that in the first case and required left tri-segmentectomy with R0 resection; however, insufficient liver function made liver resection impossible. An atezolizumab plus bevacizumab regimen was administered, and after seven courses of treatment, porta hepatis compression regressed, following which left lobectomy was performed with adequate surgical margins. The pathological diagnosis was moderately differentiated HCC, most of which was necrotic, and R0 resection was confirmed. Conclusions Atezolizumab plus bevacizumab therapy has the potential to facilitate radical resection in patients with uHCC.